Gallstones in patients older than 70 years: About 128 cases - Davidenko, Nicolás; Cresseri de Ríos, Aída; Morales, Adhemar; Pratto, Eduardo; Solé, Luis Alberto (Cirugía del Uruguay, 1986)
Study of 128 patients ovar 70 years old wlth billary llthlasls, among whlch 26 were by medical bloodless procedures and 102 were operated: 61 under coordlnallon and 41. In emergency, wllh a mortality rate of 9,83% and 41,46% respectively. The dltferent factors meanlng rlsk are enumerated, namely: social, cllnical, derivad from the surgical procedure, anatomlc, bacterlologlcal, operatlve and postoperativa, whlch may be single or mulllple and bearing a dlrect relatlon wlth mortallty rete.